The “King” of Philippine Comedy: Some Notes on Dolphy and the Functions of Philippine Cinematic Humor as Discourse - Ancheta, Maria Rhodora G. (Humanities Diliman: A Philippine Journal of Humanities, 2007)
This paper aims to come up with a valuation of Dolphy’s role as a comic artist, in terms of his function in the creation of Philippine film comedy, positing that Dolphy’s popularity as “king” of Philippine comedy is symbiotic with the inscription of comedy in terms of the functions it plays within Philippine society. While Dolphy’s iconic popularity has largely been appended to the roles or characterizations he has played over the years, and has been mainly, if not stereotypically, attributed to his personal exploits, this paper explores how this comic image, superimposed on the media hype that surrounds Dolphy’s own colorful life, moves beyond his career’s longevity or the controversies therein. Dolphy’s long and significant comic history in Philippine cinema has become a virtual template of what succeeds by way of the comic in Philippine popular visual media. While the predictability of his comedy petrifies him and ultimately limits the possible transformative value of his comedy, and while his reign as “king of Philippine comedy” is an appellation that may have begun as media hype, Dolphy can still be rightly valorized as “king” for the moment, for opening comic spaces for transgression/aggression in Philippine life.
Keywords: humor, incongruity, transgression, Philippine cinematic history, Dolphy